The Correlation between Psychosocial Stress and Prematurity - Renny Aditya (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: This study was aimed to analyze the relationship between the level of psychosocial stress on preterm birth and term birth. Methods: This was a cross-sectional study, with 45 patients experiencing preterm birth and at term birth, who met the inclusion and exclusion criterias in Obstetrics and Gynecology Department of Dr. Hasan Sadikin Hospital and other hospital nearby. Result: The level of psychosocial stress on preterm birth was severe 64.4 %, moderate 14% and mild 2%. The comparison between the group resulted in p < 0.001 using chi-square test with confidence interval 95% and correlation coefficient was phi = 0.811. The specific psychosocial stressor were problem with in laws (p=0.001), problem with husband (p=0.003), foreclosure on a mortgage or loan (p=0.001), change in residence (p=0.001), major change in living conditions (building a new home, remodeling) (p=0.001), no monetary possession (p=0.001), major change in financial state (p=0.004), environment vulnerability (p=0.035), and being dismissal from work (p=0.014). Conclusion: The relationship between psychosocial stress and preterm birth was significant. The stressor included problem with in laws foreclosure on a mortgage or loan, change in residence, major change in living conditions (building a new home, remodeling, no monetary possesion, major change in financial state, environment vulnerability, and dismissal from work. [Indones J Obstet Gynecol 2012; 36-2: 55-60] Keywords: preterm birth, psychosocial stres